Molecular Modelling and Vibrational Investigations of Ammonium-Based Ionic Liquid (CLTOAB) - Çelik, Sefa; Akbayrak, Ali Tuğrul; Özel, Ayşen E.; AKYÜZ, SEVİM (My University, 2019)
CLTOAB is an ammonium-based ionic liquid composed of ε-Caprolactam (CL) C6H11NO and tetraoctylammonium bromide (TOAB) (C32H68BrN).In this study, experimental IR and Raman spectra of CLTOAB ionic liquid together with the computational results of the compound have been reported. The optimized geometry, vibrational frequencies, IR intensities and Raman activities of the CLTOAB were calculated using the wb97xd and B3LYP density functional methods combined with the 6-31G(d,p) basis set using Gaussian 03 program. The complete assignment of the bands was performed based on the potential energy distributions (PED%). The HOMO and LUMO analysis is used to determine the charge transfer within the molecule. The Gauge-including atomic orbital 1H-NMR and 13C-NMR chemical shifts calculations were carried out and compared with the experimental data. Furthermore to evaluate interaction between CLTOAB and DNA, molecular docking study was carried out.
Keywords: Ammonium-based ILs; CLTOAB; DFT calculations; Vibrational analysis